Role of Platelet-rich Plasma in Unexplained Recurrent Implantation Failure – A Systematic Review and Meta-analysis of Randomised Control Trials - Harpreet Kaur; Meenakshi Meenu; Shivam Pandey; Anil Chauhan; Mishu Mangla (Journal of Human Reproductive Sciences)
Background: Recurrent implantation failure (RIF) is a challenging clinical situation and various strategies have been tried to improve the pregnancy rate in RIF. Platelet-rich plasma (PRP), which is obtained from the autologous blood samples of a person and is multiple times richer in platelets and other growth factors helps improve endometrial receptivity. Objective: This study has been conducted to summarise the evidence and quality of evidence available so far regarding the role of PRP in cases of unexplained RIF. Materials and Methods: An electronic database search for randomised clinical trials comparing PRP against routine care in women with unexplained RIF was performed on PubMed, EMBASE, SCOPUS and Cochrane Central. Two independent reviewers conducted a literature search and retrieved data using the predefined eligibility criteria. Bias assessment was done using the Cochrane Collaboration Network Risk of Bias Tool version 2. The quality of evidence was determined and a summary of the findings table was prepared for individual outcomes using GRADEpro software. Results: We identified 1146 records, and after removing duplicates, 531 records were screened. Out of these, 22 studies reached full-text screening and nine studies were included in the final review. We are uncertain about the effect of PRP due to the very low quality of evidence and we have little confidence that the administration of PRP had any significant effect on improving the live birth rate in women with RIF (odds ratio [OR]: 7.32, 95% confidence interval [CI]: 4.54–11.81, I2 = 40%). Similarly, the quality of evidence was low for the clinical pregnancy rate, so we are uncertain if the administration of PRP had any significant effect on the clinical pregnancy rate (OR: 3.20, 95% CI: 2.38–4.28, I2 = 0%). Interpretation: The current review suggests that there may be some beneficial effects of PRP in women with RIF, but the quality of evidence is very low and we are uncertain of the benefit and have little confidence in these findings. Limitations: Limitations are the small sample size of most studies, a short follow-up period, non-uniformity in the definition of outcomes and very low quality of evidence. Registration: The protocol was registered on PROSPERO (CRD42021292209).